Correlates of Hepatitis B infection in pregnant women attending antenatal clinics in Wa Municipality, Ghana. - Emmanuel Anebakwo Awiah; Simon Aabalekuu; Frederick Dun-Dery; Elvis Dun-Dery; Fidelis Bayor; Martin Nyaaba Adokiya; Barnabas Bessing (Public Library of Science (PLoS), 2024)
Despite the availability of an effective vaccine against viral hepatitis B infection, it remains prevalent, highly transmissible especially through mother-to-child, life-threatening, and a major public health challenge. A positive Hepatitis B e-Antigen (HBeAg) mother has a 90% risk of transmitting the virus to the unborn child in the perinatal period. This study sought to determine the prevalence and risk of Hepatitis B infection among pregnant women in the Wa Municipality of Ghana. A cross-sectional study employing systematic random sampling was conducted among 183 consented pregnant women who went for antenatal care in nine health facilities in the Wa Municipality. A structured validated questionnaire was used to collect information about socio-demographic and obstetric characteristics, awareness of Hepatitis B Virus (HBV) transmission and its prevention. Blood samples (3.0 mls) were collected from each participant to test for HBV serum markers using a Wondfo One Step HBV rapid immunochromatographic assay (Catalog number W003) for the Hepatitis B surface antigen (HBsAg). We conducted descriptive statistics including the prevalence and used multivariable logistic regression to determine the risk of Hepatitis B among study participants. Data was analysed using Stata/SE 15. About 20.2% of the 183 pregnant women screened tested positive for HBsAg. Generally, compared with younger pregnant women, older (> = 25) pregnant women were >9 times less likely to test positive for both chronic Hepatitis B core antibody (HBcAb) and (HBeAg) Hepatitis B infections. However, pregnant women in polygamous relationship were more likely to test positive for both (HBcAb) and (HBsAg and HBeAg) Hepatitis B infections compared with those in monogamous relationship. In a multivariable analysis, pregnant women in a polygamous relationships were about 5 times more likely to test positive for HBsAg (AOR = 4.61, 95% CI: 2.06-9.89) and HBcAb (AOR = 4.89, 95% CI:1.52-6.81) and HBeAg (AOR = 4.62, 95% CI:1.21-6.39) compared with those in a monogamous relationship. This study highlights a high HBsAg prevalence among pregnant women with those in polygamous relationship and younger age more likely to test positive. Facility and community-based health services should emphasize the need for regular screening, education, and vaccination of pregnant women, especially those at high risk, to prevent mother-to-child transmission of viral hepatitis B.